Building a Credential Exchange Infrastructure for Digital Identity: A Sociohistorical Perspective and Policy Guidelines - Chango, Mawaki (Frontiers in Blockchain, 2022)
Credential Exchange Infrastructures based on open standards are emerging with work ongoing across many different jurisdictions, in several international standards bodies, in industry associations with global membership, and at national level, etc. This article addresses the technology advances on this topic, particularly around identification mechanisms and the Self-sovereign identity model. It also addresses institutional aspects and make (at the very end) clear recommendations to policy makers. Rooted in a sociohistorical culture of inquiry, the goal of the article is to bring emerging digital identity systems within the grasp of a wider public as well as to contribute to mutual understanding across stakeholder groups about what is at stake. This is expected to enhance their capacity to better navigate across the pitfalls of this transition period between paper and digital systems and toward the full adoption of the latter, with each of these stakeholders playing a part in enabling trust around digital identity infrastructure and transactions, both within related ecosystems and in the broader society. In addition to defining and elaborating on the concepts of identity, credential and trust, this article makes contributions around three axes. First axis is conceptual and analytical. The article identifies three conceptual phases in the evolution of identity practices in history with the hypothesis that the availability of new record-creation methods invites changes in, and expansion of, the existing identification processes. This helps make a stronger case for why the Internet needs an identity capability. The second axis of the article is a case study on self-sovereign identity as instantiated through the Sovrin network. The case study presents the technology and its design with a view to enabling a non-technical public to understand what it is and how it works, while highlighting the fact that the technology still needs institutional processes to make it work as intended. The final axis of this article provides guidelines to policy actors potentially facing the need to enable large scale implementations of these emerging technologies, as they mature. Policy-makers approaching this material may want to read this section first and then return to the rest of the paper.